Effect of sward height on the fermentability coefficient and chemical composition of Guinea grass silage - Tomaz, P. K. [UNESP]; de Araujo, L. C. [UNESP]; Sanches, L. A. [UNESP]; dos Santos-Araujo, S. N. [UNESP]; de Lima, T. O. [UNESP]; Lino, A. de A. [UNESP]; Ferreira, E. M. (Wiley, 2018)
There is a high correlation between sward height and pasture sward structure. Therefore, in tropical grasslands, taking sward height into account has been a much better strategy in rotational stocking management than considering pre-defined days of growth. Similarly, sward height could be used to determine the moment when tropical grasses present the best ensilability parameters. This study aimed to identify the sward height at which Panicum maximum cv. Mombaça (Guinea grass) provides the highest fermentability coefficient (FC) and to define the combination of additives that best improves the chemical composition of silage. Two trials were carried out in Selvíria, MS, Brazil, from 2015 to 2016. The first year was used to identify the highest FC, and the second year was used to identify the best combination of eight additives (citrus pulp [CIP], homofermentative and heterofermentative LAB, their combinations and control). Statistical analyses were performed using SAS (p <.05), and one contrast was defined as silage with CIP vs. silage without CIP. The height of 130 cm resulted in the highest FC (31.01). Silages inoculated with CIP had better quality than silages without CIP, due to the high crude protein (8.3 vs. 7.3% DM), DM recovery (98.6 vs. 93.3% DM), low pH (3.92 vs. 4.91) and NH3-N values (2.49 vs. 14.73% total N). Sward height is a consistent parameter for determining the time of ensiling Guinea grass, and the inclusion of CIP is necessary to raise the silage quality.
Keywords: citrus pulp; Lactobacillus; microbial inoculant; pasture ecophysiology; randomized block design